2020
DOI: 10.1590/1414-462x202028010319
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao descontrole glicêmico de diabetes mellitus em pacientes atendidos no Sistema Único de Saúde no Sudoeste da Bahia

Abstract: Resumo Introdução O diabetes mellitus constitui importante problema de saúde pública, responsável por grande morbidade e ônus significativo à saúde pública. A hemoglobina glicada, que avalia a glicemia média nos últimos sessenta dias, tem sido importante ferramenta na prevenção das comorbidades. Objetivo Avaliar a prevalência do descontrole glicêmico e metabólico e fatores associados em indivíduos atendidos em um laboratório central do sudoeste da Bahia Método Trata-se de estudo transversal realizado com 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
4
0
9
Order By: Relevance
“…(19) The association of elevated HbA1c with physical inactivity was also evidenced in a study conducted in Southwestern Bahia, Brazil. (4) This association was expected, as evidence shows that inactive individuals or those with a low level of physical activity present worse glycemic levels. (20) Physical activity is one of the pillars in the treatment of chronic noncommunicable diseases, as it brings benefits in reducing mortality rates from cardiovascular diseases and preventing complications.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…(19) The association of elevated HbA1c with physical inactivity was also evidenced in a study conducted in Southwestern Bahia, Brazil. (4) This association was expected, as evidence shows that inactive individuals or those with a low level of physical activity present worse glycemic levels. (20) Physical activity is one of the pillars in the treatment of chronic noncommunicable diseases, as it brings benefits in reducing mortality rates from cardiovascular diseases and preventing complications.…”
Section: Discussionmentioning
confidence: 84%
“…(3) Type 2 diabetes mellitus can be the result of multiple factors, such as behavioral aspects (overweight, obesity, alcohol consumption, smoking), diet (refined carbohydrates and sugary foods, saturated fats), physical activity (physical inactivity, sedentary lifestyle), knowledge about one's own health/disease condition, and self-care (non-adherence to health promotion and maintenance actions). (4) As a result, people with DM2 find it difficult to control in their daily lives, which requires trained professionals to assist them. In Brazil, a study conducted in 38 Basic Health Centers found that 69.8% of participants had uncontrolled DM2, (5) as in other countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…É necessário que as práticas de saúde relacionadas ao controle da glicemia e prevenção de comorbidades, métodos de educação em saúde, entre outros, sejam efetivamente postos em prática e a equipe de saúde esteja conscientizada e envolvida na necessidade de que os pacientes atinjam as metas de controle pré-estabelecidas pelas diretrizes das Sociedades médicas e orientações do Ministério da Saúde. Dessa forma, poderá gerar impacto na diminuição de comorbidades associadas, melhoria da qualidade de vida e menor impacto nos custos da saúde, como as complicações micro e macrovasculares do diabetes (Souza & Oliveira, 2020).…”
Section: Discussionunclassified
“…O Diabetes Mellitus (DM) está inserido dentro do contexto das doenças crônicas não transmissíveis (DCNT), essa patologia caracteriza-se por uma condição metabólica marcada por quadros de hiperglicemia, devido a uma falha na produção de um hormônio chamado insulina, responsável pela regulação da glicose no sangue ou em uma situação chamada de resistência à insulina. Sua classificação se dá em subtipos: DM tipo 1, tipo 2 e gestacional, dentre esses destaca-se o tipo 2 como sendo a principal causa de mortes no mundo associada ao Diabetes Mellitus (Souza & Oliveira, 2020). Aliado a isso, é possível afirmar que a população mundial acometida pelo DM atualmente está estimada em aproximadamente 387 milhões, como esses números vêm crescendo no decorrer dos anos a expectativa é que em 2035 ultrapassem os 470 milhões de casos.…”
Section: Introductionunclassified